PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH DAN DAMPAKNYA TERHADAP LOYALITAS NASABAH TABUNGAN TANDA 360 BANK OCBC NISP CABANG HARCO MANGGA DUA - Emiliawati Muslimah dan Wahyu Murti (Jurnal Manajemen FE-UB, 2017)
Customer satisfaction is a top priority in this study because of the sharper rate among banking company in Indonesia. The main thing for the company to survive, compete and dominate the market, the quality of product and service quality should be improved. Banking must pay attention to things that are important to customers. That customers are satisfied and do not switch to the other banks. The study aims to determine the effect of product quality, service quality and customer satisfaction as well as its impact on customer loyalty Bank OCBC NISP Branch Harco Mangga Dua.The data used in this study are primary data collected from questionnaires that have been distributed and filled out by customers. Data processing method using path analysis (path analysis) with the aid of an analysis tool SPSS Version 20.0.Results showed simultaneous variable product quality, service quality and customer satisfaction and significant positive effect on customer loyalty. Partially indicates that there is a positive and significant effect on the quality of products to customer satisfaction. There is a positive and significant influence between service quality on customer satisfaction. There is a positive and significant influence between product quality on customer loyalty. There is a positive and significant influence between service quality on customer loyalty. Keywords : Product Quality, Service Quality, Customer Satisfaction and     Customer Loyalty